Techno-economic viability of integrating satellite communication in 4G networks to bridge the broadband digital divide - Asma Chiha; Marlies Van der Wee; Sofie Verbrugge; Didier Colle (International Telecommunications Society (ITS), 2018)
Bridging the broadband digital divide between urban and rural areas in Europe is one of the main targets stated in the Digital Agenda for Europe. Though many solutions are proposed in literature, satellite communication has been identified as the only possible solution for rural areas, due to its global coverage. However, deploying an end-to-end satellite solution might be in some cases not cost-effective. In this paper, we propose a converged solution that combines satellite communication as a backhaul network with 4G as a fronthaul network to bring enhanced broadband connectivity to European rural areas. Therefore, a techno-economic model is proposed to analyze the viability of this integration. The model is based on a Total Cost of Ownership (TCO) model for 5 years, taking into account both the capital and the operational expenditures, designed for converged networks. This model aims to calculate the TCO as well as the Average Revenue Per User (ARPU) for the studied scenarios. We evaluate the suggested model by simulating a hypothetical use case for two scenarios. The first scenario is based on a radio access network connecting to the 4G core network via a satellite link. Results for this scenario show high operational costs. In order to reduce these costs, we propose a second scenario, consisting of caching the popular content on the edge to reduce the traffic carried over the satellite link. This scenario demonstrates a significant operational cost decrease (more than 75%), which also means a significant ARPU decrease.
Keywords: 330; Techno-economics; broadband digital divide; satellite; 4G